High biological species diversity in the arctic flora - Grundt, Hanne Hegre (National Academy of Sciences, 2006)
The arctic flora is considered to be impoverished, but estimates of species diversity are based on morphological assessments, which may not provide accurate counts of biological species. Here we report on crossing relationships within three diploid circumpolar plant species in the genus Draba (Brassicaceae). Although 99% of parental individuals were fully fertile, the fertility of intraspecific crosses was surprisingly low. Hybrids from crosses within populations were mostly fertile (63%), but only 8% of the hybrids from crosses within and among geographic regions (Alaska, Greenland, Svalbard, and Norway) were fertile. The frequent occurrence of intraspecific crossing barriers is not accompanied by significant morphological or ecological differentiation, indicating that numerous cryptic biological species have arisen within each taxonomic species despite their recent (Pleistocene) origin.